THE INFLUENCE OF FORMULA MILK PROMOTION, THE ROLE OF HEALTH WORKERS, AND MOTHER'S ATTITUDES TOWARDS EXCLUSIVE BREASTFEEDING - Diah Ayu Lestari; Turiyani; Nesa Ayu Murthisari Putri (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Exclusive breastfeeding is an essential intervention for improving infant health and development. However, exclusive breastfeeding coverage in Indonesia remains below national targets and Sustainable Development Goals (SDGs) standards. This quantitative descriptive-analytical study used a cross-sectional approach involving 80 breastfeeding mothers with infants aged 0–6 months at PMB Irma Iryani, in February 2025. Data were analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS). The coefficient of determination (R²) was 83.7%. Formula milk promotion had the most dominant direct influence (21.42%), followed by maternal attitudes (12.77%) and the role of health workers (7.05%). All hypotheses were accepted (T-statistic > 1.96; p < 0.05). Formula milk promotion, the role of health workers, and maternal attitudes significantly influence exclusive breastfeeding practices. Strengthening lactation education and stricter monitoring of formula milk promotion in health facilities are recommended.